Fifth disease with biphasic clinical course. - Ferrara, M.; Russomando, M. (European Journal of Pediatric Dermatology, 2005)
Fifth disease is due to human Parvovirus B19. From a clinical point of view, the exanthem usually evolves in three stages (1, 2). The first stage is characterized by bright, merging erythema of the face, simulating slapped cheek, often associated with "circumoral pallor". The second stage, occurring 1 - 4 days later, is characterized by generalization of the exanthem, mainly affecting the root of the limbs and tending with days to show a reticulate pattern. The third stage, which can last 1 or several weeks, is characterized by a waxing an waning clinical course of the exanthem. Arthralgias and arthritis can be present (4), as well as anemia and transient aplastic crises, the latter being more frequent in subjects with concomitant hematological disorders (1, 2). In our case with unusual biphasic clinical course, the responsibility of Parvovirus was confirmed by the family history and serological studies.